La dimensión pragmática del lenguaje de la saturación en la fenomenología de Jean-Luc Marion - Pizzi, Matías (2024)
The aim of this article is to address Jean-Luc Marion’s interpretation of the pragmatic tradition, in order to demonstrate the practical dimension of French eventual phenomenology. First, we will explore the passages where Marion develops this critical appropriation of pragmatism. We will show, on the one hand, that this reception is inseparable from his reading of the thought of Dionysius the Areopagite, as can be seen in L’Idole et la distance (1977) and De surcroît (2001). On the other hand, we will investigate his reading of pragmatism and the Speech Act theory in Le visible et le révélé (2005). In order to clarify the singularity of this reception practiced by Marion, we will simultaneously provide an analysis of analytical pragmatism, particularly considering Richard Rorty’s proposal. Finally, we will expand the language pragmatics of saturation in Marion to various common issues in Jean-Louis Chrétien’s phenomenology of the voice, as both proposals express a performative and non-predicative language that emphasizes the excess of meaning outside the paradigm of objectivity.